A 10-year single-center audit of cell saver use in cardiac surgery: Single-center audit of cell saver use in cardiac surgery - Otorkpa, Michael; Mahmood, Zahid (Journal of Surgery and Medicine, 2025)
Background/Aim: The use of cell saver technology has revolutionized the management of blood in cardiac surgery, with the objective of reducing the need for allogeneic blood transfusions and enhancing patient outcomes. This study presents a 10-year audit of cell saver use in cardiac surgeries at a tertiary cardiothoracic center in Scotland. Methods: An analysis of data from cardiac surgery cases using cell savers was conducted. The study assessed the quantity of anticoagulant used, the processing of blood, and the recovery of red blood cells. Results: The center consistently employed heparin as the anticoagulant during the review period. The mean age of the 1717 patients was 56.85 years; 66.86% were male and 33.14% were female. The mean blood processed volume was 1646.55 ml and the mean salvaged red cell volume was 544.22 ml over a 10-year period. The deployment of cell savers was most prevalent during coronary artery bypass graft surgeries and major aortic procedures. Conclusion: The potential to minimize blood loss and reduce allogeneic blood transfusions is present in cell saver technology for cardiac surgery. The significance of optimizing cell saver protocols to enhance patient care and efficacy is underscored in the study.